Simulation models for MIMO wireless channels - Hua Li; Jing Bai; Shujian Liao; Juanping Wu (Institute of Advanced Engineering and Science, 2013)
In recent years, with the excellence performance in the system spectrum efficiency, MIMO technology has become the concerned topic in the mobile communication technology development process. In order to make better use of MIMO technology, the characteristics of MIMO channel had to be studied, and it is inevitable to accurately model and simulate MIMO wireless channels in different conditions. Wireless communication environment is very complex, so it is difficult to modeling of MIMO channel. In this paper, carrier wave frequency, the maximum Doppler frequency shift, AOA (Angle of Arrival) distribution, power azimuth spectrum and adjacent antenna spacing were token into account integrating. Expressions of the spatial correlation coefficient for different power azimuth spectrum (PAS) distributions were studied. A MIMO channel model was brought forward which has spatial selectivity, frequency selectivity, and time correlation. Simulation shows this related channel capacity is consistent with theoretical channel capacity. Thereby the rationality of this modeling was validated. This model provides powerful implement for simulation of MIMO capability, analysis of system capacity and evaluation of performance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1883